Potency of Tokishakuyakusan in treating preeclampsia: Drug repositioning method by in vitro screening of the Kampo library - Yagi, Kazunobu (PLoS One, 2020)
INTRODUCTION: Preeclampsia therapy has not been established, except for the termination of pregnancy. The aim of this study was to identify a potential therapeutic agent from traditional Japanese medicine (Kampo) using the drug repositioning method. MATERIALS AND METHODS: We screened a library of 74 Kampo to identify potential drugs for the treatment of preeclampsia. We investigated the angiogenic effects of these drugs using human umbilical vein endothelial cells (HUVECs). Enzyme-linked immunosorbent assays were performed to measure the levels of placental growth factor (PlGF) in conditioned media treated with 100 μg/mL of each drug. We assessed whether the screened drugs affected cell viability. We performed tube formation assays to evaluate the angiogenic effects of PlGF-inducing drugs. PlGF was measured after administering 10, 50, 100, and 200 μg/mL of the candidate drug in the dose correlation experiment, and at 1, 2, 3, 6, 12, and 24 h in the time course experiment. We also performed tube formation assays with the candidate drug and 100 ng/mL of soluble fms-like tyrosine kinase 1 (sFlt1). PlGF production by the candidate drug was measured in trophoblastic cells (BeWo and HTR-8/SVneo). The Mann-Whitney U test or one-way analyses of variance followed by the Newman-Keuls post-hoc test were performed. P–values < 0.05 were considered significant. RESULTS: Of the 7 drugs that induced PlGF, Tokishakuyakusan (TS), Shoseiryuto, and Shofusan did not reduce cell viability. TS significantly facilitated tube formation (P = 0.017). TS administration increased PlGF expression in a dose- and time-dependent manner. TS significantly improved tube formation, which was inhibited by sFlt1 (P = 0.033). TS also increased PlGF production in BeWo (P = 0.001) but not HTR-8/SVneo cells (P = 0.33). CONCLUSIONS: By using the drug repositioning method in the in vitro screening of the Kampo library, we identified that TS may have a therapeutic potential for preeclampsia. Its newly found mechanisms involve the increase in PlGF production, and improvement of the antiangiogenic state.